PEMBERDAYAAN PONDOK PESANTREN MELALUI BUDIDAYA IKAN LELE SEBAGAI WIRAUSAHA SANTRI - ZUBAIDAH, SITI; -, SURIANSYAH; -, SUSTIYAH; ASIE, KAMBANG VETRANI (Buletin Udayana Mengabdi; Vol 14 No 1 (2015): Jurnal Udayana Mengabdi, 2015)
Hidayatullah and Hidayatul Insan pondok pesantren have many students, however, it has not yet had independent business to increase the financial, although the land area owned is quite extensive. The students were introduced by growing the fish-pond with catfish program. Catfish tastes good, contains high nutrient and easily cultivated. Age range 3 month. The problem in catfish farming is a matter of artificial feed is expensive. Feed costs about 60-70 % of the total fishery production costs . The objectives of IbM is providing skills to the students in catfish farming and fish feed manufacturing . Method used: Counseling, Training manufacture of fish feed , catfish Practice and Guidance. The results showed that the implementation of IbM catfish farming quite successfully and yields about 50 pounds of 500 fingerlings are stocked. Yields are low because there are deaths due fingerlings acclimatization process is not optimal, non-uniform large seeds so that the seeds are tiny edible seeds of a larger size. Catfish growth is quite good because the fish feed protein content of not less than 30 %. After training 83.33 % - 92.86 % of students want to make their own fish feed for catfish. Keywords: Pondok Pesantren, catfish, fish feed